A Robustness Analysis of Automated Essay Scoring Methods - Anchiêta, Rafael T.; de Sousa, Rogério F.; Moura, Raimundo S. (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2024: Anais do XV Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana, 2024)
This paper analyzed the robustness of a state-of-the-art Automated Essay Scoring (AES) model by applying various linguistically motivated perturbations to the Essay-BR corpus. Our findings reveal that the AES model failed to detect these adversarial modifications, often assigning higher scores to the disturbed essays than to the original ones.